2004
DOI: 10.1002/bjs.4457
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic expression of a family with multiple endocrine neoplasia type 2A due to a RET mutation at codon 618

Abstract: Because of the great interindividual differences in tumour aggressiveness within the family it is impossible to predict whether an individual gene carrier will have an aggressive MTC or not. This unpredictability is an additional argument, besides those obtained in stratified genetic studies, for operating on gene carriers at young age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…)Current series(Ref. )918 RL 31.130.75 [9]112.7 [15]634 RL 21.251.1 [15]75 [15]611 RL 263 [9]28 [21]620 RL 265 [10]22 [15]618 RL 2127 [9]11 [10, 22, 23]804 RL 16 [24]6 [24] MTC medullary thyroid carcinoma, LN lymph node metastasis; -, not observed, RL risk level of MTC based on the 1999 consensus statement from the Seventh International Workshop on Multiple Endocrine Neoplasia [11, 15]…”
Section: Resultsmentioning
confidence: 99%
“…)Current series(Ref. )918 RL 31.130.75 [9]112.7 [15]634 RL 21.251.1 [15]75 [15]611 RL 263 [9]28 [21]620 RL 265 [10]22 [15]618 RL 2127 [9]11 [10, 22, 23]804 RL 16 [24]6 [24] MTC medullary thyroid carcinoma, LN lymph node metastasis; -, not observed, RL risk level of MTC based on the 1999 consensus statement from the Seventh International Workshop on Multiple Endocrine Neoplasia [11, 15]…”
Section: Resultsmentioning
confidence: 99%
“…diagnosis at age 27 and 26 (36); both are still alive with MTC 27 and 28 years later. Preoperative calcitonin levels were not reported.…”
Section: Fig 1 Study Schemamentioning
confidence: 99%
“…Such mutations are explicitly located in cysteines within this extracellular cysteine-rich domain and give rise to the subtype of MEN2A [12]. Codon 618 with p.Cys618Arg, p.Cys618Gly and p.Cys618Ser and to a lesser extent with codons p.Cys618Phe and p.Cys618Tyr, have been associated with the greatest rates of pheo [13][14][15]. Some studies revealed that the severity of pheo due to mutations in codons 609, 618 and 620 can be as aggressive as the one that is usually shown by the five amino acid substitutions at codon 634.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies revealed that the severity of pheo due to mutations in codons 609, 618 and 620 can be as aggressive as the one that is usually shown by the five amino acid substitutions at codon 634. However, the majority of the cases, demonstrated greatest expression for 634, followed in decreasing order by codons 618, 620 and 609 [13,16,17]. In recent reports, the spectrum of mutations identified in the RET proto-oncogene in patients with MTC has shifted from the 'classical' and most prevalent worldwide mutation at codon 634 in exon 11 to clinically less aggressive forms with mutations in exons 13-15 [18][19][20].…”
Section: Introductionmentioning
confidence: 99%